RELIABILITY ANALYSIS OF A TRAM LINE - Koyun, Ayhan; Kaymakci, Ozgur Turay (GAZI UNIV, FAC ENGINEERING ARCHITECTURE, 2015)
In railway systems which traction power system and transmission type of the power have a critical importance, priority target is that supplying continuity of operation by obtaining a reliable traction power which the system need. This can only be achieved by the operation of the traction power system components with minimal faults. In this scope, failure modes of the traction power supply system components which are used within the railway systems must be determined, risks which these failure modes will cause should be exposed, safety functions that prevent unacceptable risks should be implemented and as a result the system must be reached to the required level of the safety for high availability and safety. In this study, sub-systems that located in the traction power supply system were examined in the scope of the traction power supply system of the Kabatas - Bagcilar T1 tram line that is operated by Istanbul Transportation Co., failure modes were analyzed, Markov models have been created for sub-systems and reliability values were calculated for corresponding sub-systems. In addition, safety analysis of the whole system is made by getting the results that are obtained in the light of the models as a reference.
Keywords: Traction systems; reliability; continuity of operation; railway system; Markov models; fault tree analysis; Engineering